Associations between neck circumference and markers of dysglycemia, non-alcoholic fatty liver disease, and dysmetabolism independent of Body Mass Index in an Emirati population - Fojas, Esphie Grace Fodra; Buckley, Adam John; Lessan, Nader (Frontiers in Endocrinology, 2022)
Aim: Neck circumference (NC) is quick and easy to measure and may be a useful surrogate marker for body composition. We investigated NC as a potential marker of dysglycaemia, MetS and NAFLD. Methods: 674 individuals were recruited at Imperial College London Diabetes Centre in a study of sleep apnoea prevalence. Of these, 547 (Age 46 ± 11.4 years, Body Mass Index (BMI) 31 ± 6 kg/m2, 279 (51%) female, 113 normal glucose tolerance (NGT), 108 Prediabetes, 326 Type 2 diabetes (T2DM)) met all inclusion criteria for analysis. NC was measured at the thyroid cartilage, and collar size was recorded. Analysis was performed using univariate and multivariate linear regression. Results: Adjusted for BMI, sex and age, NC was 0.65±0.3 cm greater in prediabetes (p=0.0331), and 1.07±0.28 cm greater in T2DM, compared with NGT (p=0.0002). Adjusting for BMI, sex, and glycaemic status, 1 cm increase in NC was associated with a 1.04±1.01 U/L (p<0.0001) increase in ALT, and additionally correcting for statin use, a 0.03±0.01 mmol/L reduction in HDL (p<0.0001) and a 0.1±0.02 increase in TC:HDL. A 1 cm increase in NC was associated with a 1.15±1.02 % (p<0.0001) increase in 10 year AHA cardiovascular risk in individuals over 40 years old and a 0.16±0.02 (p<0.0001) increase in NAFLD fibrosis score. Neck circumference was associated with hazard of new onset of deranged ALT adjusted for age, sex, glycaemic status, and BMI (hazard ratio 1.076 (95% CI 1.015-1.14, p=0.0131) and with incidence of Fatty Liver Index associated with high probability of NAFLD (hazard ratio 1.153 (95% CI 1.019-1.304), p=0.0239). Conclusion: NC is associated with dysglycaemia, components of the MetS and factors predictive of NAFLD but does not appear to independently predict subsequent progression to high risk of liver fibrosis in this predominantly diabetic population.